2017
DOI: 10.1016/j.cub.2016.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Mechanisms of a Retinal Ganglion Cell with Stimulus-Dependent Response Latency and Activation Beyond Its Dendrites

Abstract: SUMMARY Center-surround antagonism has been used as the canonical model to describe receptive fields of retinal ganglion cells (RGCs) for decades. We describe a newly identified RGC type in mouse, called the ON delayed (OND) RGC, with receptive field properties that deviate from center-surround organization. Responding with an unusually long latency to light stimulation, OND RGCs respond earlier as the visual stimulus increases in size. Furthermore, OND RGCs are excited by light falling far beyond their dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 49 publications
5
69
2
Order By: Relevance
“…Nine of our internally validated types (5ti, 5so, 5si, 4i, 4on, 6sn, 7o, 73, 82wi) correspond with GC classes that were recently defined by physiological and anatomical techniques (Baden et al, 2016; Jacoby and Schwartz, 2017; Mani and Schwartz, 2017; Sabbah et al, 2017) but have not yet been confirmed as pure types by molecular techniques and mosaic analysis. Our density conservation test (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Nine of our internally validated types (5ti, 5so, 5si, 4i, 4on, 6sn, 7o, 73, 82wi) correspond with GC classes that were recently defined by physiological and anatomical techniques (Baden et al, 2016; Jacoby and Schwartz, 2017; Mani and Schwartz, 2017; Sabbah et al, 2017) but have not yet been confirmed as pure types by molecular techniques and mosaic analysis. Our density conservation test (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Our 7o corresponds to the nonclassical transient On DS cell found by Baden et al (2016) and Sabbah et al (2017). Our 73 corresponds to the On delayed cell as defined by Mani and Schwartz (2017). Our 82wi corresponds to the vertically orientation selective cell studied by Nath and Schwartz (2016).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Further, ON-delayed (n = 21, Figure 1C) and OFF-delayed (n = 211, Figure 1G) RGC types were differentiated based on their delayed response kinetics with >0.3 s latencies. Responses of these RGCs were reminiscent of previously described ON-and OFF-delayed RGCs [40]. Following characterization, firing pattern maps of population of RGCs were created and recorded for ON, OFF, ON-OFF and ON/OFF-delayed RGC responses to specify their positions over the MEA in the following experiments.…”
Section: Characterization Of Major Rgcs/displaced Ac Populations In Tmentioning
confidence: 99%
“…showed increased activity) suggests that this is a highly specific property, presumably because the chromatically nonlinear cells comprise specific subtypes of ganglion cells and likely only few (perhaps a single type at least for the rare nonlinear On cells). Despite the hypothesis that nonlinear chromatic integration is cell-type specific, the measured chromatic nonlinearity indices did not fall into discrete groups, but formed a continuum, reminiscent of characterizations of spatial integration (Carcieri et al, 2003;Mani and Schwartz, 2017).…”
Section: Discussionmentioning
confidence: 82%